COMMUNICATIONS THE PANGS OF GENDER POLITICS - Couillard, Marie-Andree (Penerbit USM, 1991)
"Dissident" interpretation of men-women relations among rural Malays of the past (dissident with regard to a certain type of feminist analysis presuming the universality of patriarchy). This interpretation is then used to offer an alternative view of their role in current development.